Hubungan Pengetahuan Ibu Dengan Pemberian ASI Eksklusif - Mustika Ayu Lestari; Nining Fatria Ningsih; Hasrun Ningsih; Elly Sustiyani (Journal of Mandalika Literature, 2024)
Basically, breastfeeding, especially exclusively, is natural for a mother who gives birth. Exclusive breastfeeding has a big contribution to the child's growth and development and immune system. A mother's knowledge of exclusive breastfeeding is an important factor for her baby. This study aims to determine the relationship between maternal knowledge in providing exclusive breastfeeding in Pengadang village. This research is a quantitative analytical survey research with a cross sectional approach taken using a purposive sampling technique, totaling 95 respondents. The results of this research are that the majority of respondents have good knowledge about exclusive breastfeeding, 44 respondents (62.9%). From the results of data analysis using the Fisher's Exact test, it was found that the P-Value was <0.05 (0.000). There is a relationship between maternal knowledge and breastfeeding in Pengadang village, Pengadang Community Health Center working area in 2023.